Effect of water temperature on embryonic development of Protunus trituberculatus in an off-season breeding mode - He, Jie; Wan, Litao; Yu, Huaihua; Peng, Yingying; Zhang, Dongxu; Xu, Wenjun (Frontiers in Marine Science, 2022)
Portunus trituberculatus (swimming crab) is an important breeding crab in China. The current breeding mode of swimming crab is still the traditional “spring seedling and winter harvest” breeding mode. In recent years, researchers have begun to explore a new off-season breeding mode through autumn seedling. In this study, the rate of embryonic development, embryo antioxidant ability and hatching rate of swimming crab in different water temperatures in an off-season breeding mode (breeding in early autumn) and digestive enzyme activity of newly hatched larvae were compared. The results showed that the duration of each development stage of swimming crab embryos was gradually reduced with increasing water temperature. The total development time was 9.43 d at 27°C and only 6.88 d at 33°C. These effects were accompanied by an increase in the development rate from 0.11 d-1 to 0.15 d-1. The total effective accumulated temperature under the 4 temperature conditions was basically maintained at about 150°C·d (147.08 ∼ 153.62°C·d), and there was no significant difference between different groups. The development of embryos at 27°C and 29°C was very synchronous, and no abnormal embryos were observed. Conversely, at 31°C, the later stage of development exhibited asynchrony, and diapause and death were noted in some embryos. At 33°C, more embryos died. The embryo hatching rate was approximately 70% at 27°C and 29°C, and the rate was significantly reduced at 31°C and 33°C. Specifically, the rate was only 13.89% at 33°C. As the water temperature increased, the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-PX) as well as the total antioxidant capacity (T-AOC) and malondialdehyde (MDA) levels of embryos increased first and then decreased, reaching the highest value at 31°C. Catalase (CAT) activity exhibited the opposite trend which was the lowest at 29 °C with a value of only 0.17 U/mg prot and the highest at 33°C with a value of up to 0.51 U/mg prot. At temperatures of 27°C, 29°C and 31°C, the differences in various digestive enzymes of newly hatched larvae primarily manifested as the high activities of pepsin (PEP) and α-amylase (AMS) at 31°C, and other differences were not obvious. At 33°C during embryonic development, the activities of various digestive enzymes were relatively low, especially the activities of trypsin (TPS) and cellulase (CL), which were significantly lower than those of the other three temperature groups. Therefore, judging from the antioxidant index of embryos and the digestive enzyme activity of newly hatched larvae, the embryonic development was still good when the water temperature was 31°C, accompanied by water temperatures above 31°C that seriously affected enzyme activity. Overall, a temperature below 31°C represents the appropriate temperature for embryonic development in autumn in swimming crabs.